OS PARADIGMAS DA ESTRUTURA CURRICULAR DAS PRIMEIRAS FACULDADES DE DIREITO NO BRASIL - Carlos Renan Moreira Bretas; Maria Alice Nunes Costa (LexCult, 2020)
This article analyzes the first Brazilian Law schools emergencein 1827 in the cities of Olinda and São Paulo. In the first half of the nineteenth century, the new courses were not significant in terms of scientific production. But in the second half of that century, there were an increase in the academic expressiveness of the faculties, especially observed in Pernambuco, when the course was transferred from Olinda to Recife in 1854. Influenced by liberal paradigms, the objective of the colleges was to form a qualified body to attend to the administrative State’s interests. If on the one hand, in Recife, it has a preponderance of presuppositions influenced by the evolutionism, scientism and culturalism, mainly due to Tobias Barreto; on the otherhand, in São Paulo, pragmatism and teaching of Civil Law prevailed, meetingthe oligarchic elites needs, with regard to contractual and property rights. Even in the second half of the nineteenth century, some reforms were implemented in the curriculum. The Catholic Church has lost influence in education and the government has notbeen able to intervene in teaching, becoming this "free".